The study of viability and growth kinetic of mycelium from various part and age of oyster mushroom (Pleurotus Sajor-caju) using tissue culture technique - Mohd Syarif Hidayatullah Azman (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Oyster mushroom ( Pleurotus sajor-caju) is one of the species of mushroom in the world. Oyster mushroom contain a lot of nutrients such as at about 85/95 % of water 3 % of protein 4 % of carbohydrates 0.1 % of fats 1 % of minerals and vitamins. There are several problems that mushrooms farmers in Malaysia always face which are lacks of yield reduction seedlings and seedlings get as many difficulties. Therefore to overcome the problems is by using the tissue culture method. The viability part of the mushroom should be determined first before applying this method. This is due to only part that have high viability have active cell tissue to grow in the media culture and can produce many and faster mycelium. From this mycelium the spawn or seedling can produce. After that the explants from at which age in first harvest must be determine before applying tissue culture method. Oyster mushrooms only need 3 days to grow before harvesting. So in between age 2 day or 3 day must be choose as explants. In other to prove at which age of the mushroom is good as mother explants growth kinetic for both of them should be measured by using general kinetic equation model.